An assessment of reported medication errors in a tertiary hospital to identify targets for patient safety improvement. - Parreno, Ma. Teresita
In this age of quality assurance in health care, the practice of patient safety is very important. It was observed that medication errors is a persistent problem and is alarming because of its serious effect to nursing practice and to the healthcare system. It may result to patient harm as well as increased healthcare costs and its indirect effects strike to the nurses' personal and professional practice. Such then will have an impact on the quality of care the nurses' rendered. The study was done to evaluate hospital system in medication administration and to find out whether the standard operating procedure in medication administration set by the institution are followed and will not cover other standards not included in their policy manual. It includes standard operating procedures in carrying out doctor's order, in dispensing medication, in actual drug administration and in documentation and monitoring. Specifically, to determine the extent of medication errors in a tertiary hospital and to identify variables affecting medication errors: a) System b) Processes. The study did not look deeper into medication errors effect on the patient. The findings of the study is hoped to guide management for training development for Patient Safety Improvement, thus improving hospital service. The study utilized the Descriptive Audit Research Design Type 2, specifically, it was designed to investigate and determine factors that resulted to committing of medication error. It examined 43 filed or reported medication errors from January 2010 to December 2012 of Maria Reyna-Xavier University Hospital Inc. through a retrospective incident report review using a modified nursing audit tool. To answer the specific problems of the study, the frequency and percentage were utilized and to substantiate the analysis, FGD with staff nurses and KII with doctors and pharmacists were done. The findings showed that majority of the patients involved in medication error belonged to the 60 and above years old age group. The error is an actual occurrence committed mostly by nurses usually happening during the PM shift. Study showed that the most common deviated SOP's were the 10 rules in the medication administration and carrying out doctor's order. Generally, the most common medication error committed were Type III error and the most common processes occurred were Transcription error, Omission to administer the drug, Wrong drug, and Wrong timing, Wrong quantity and Documentation error (Failure to chart). Major recommendations then are for the Nursing Service Department to adapt new trends in medication administration for patient safety program improvement, for Quality Assurance Committee of the Hospital to include in their Quality Review SOP's related to Drug administration and to conduct regular assessment for its compliance and to use study results in the review of drug administration process for the Nursing Service Post Graduate Training Program